The effect of unilateral chewing habit on interincisal distance of maximum mouth opening: Pengaruh kebiasaan mengunyah satu sisi terhadap jarak interinsisal bukaan mulut maksimal - Norman Hidajah; Ketut Virtika Ayu; Ervina Gisela (Makassar Dental Journal PDGI Makassar, 2021)
One of the causes of temporomandibular disorder (TMD), which is a bad habit of chewing on one side. The occurrence of TMD can be characterized by limited mouth opening of less than 40 mm. Maximum mouth opening distance can be influenced by gender, age, weight, and height. This study is intended to determine the interincisal distance of maximum mouth opening in unilateral chewing habit. By using descriptive observational study with a purposive sampling technique, it was obtained of 25 subjects, students from the Faculty of Dentistry, Mahasaraswati Denpasar University. Data collection was carried out by using a sliding caliper direct to measure the distance of interincisal when open the mouth. The results showed that 10 men (40%) had an average maximum mouth opening of 42.6 mm, 15 women (60%) had an average maximum mouth opening of 39.6 mm, 5 people (20%) with a body weight of 41-50 kg had the lowest average maximum mouth opening of 37.4 mm, 4 people (16%) with a body weight of 81-90 kg had the highest maximum mouth opening of 45.5 mm, 2 people (8%) with a body height of 151-160 cm had the lowest maximum mouth opening of 36.5 mm, 8 people (32%) with a body height of 171-180 cm had the highest maximum mouth opening of 42.3 mm and 25 people (100%) had a maximum mouth opening of 40.8 mm. It was con-cluded that there are 48% (12 people) subjects have an average maximum mouth opening distance with a limited category of 36.3 mm and 52% (13 people) subjects have an average maximum mouth opening distance with a normal category of 45 mm.